A Comparative Analysis Between Adomian Decomposition Method and Differential Transformation Method for Solving Some Second-Order Ordinary Differential Equations (Journal of Nonlinear Modeling and Analysis, 2025)
The differential transformation method (DTM) and Adomian decomposition method (ADM) are two numerical methods that can be used tosolve various differential equations. In this work, we compare the accuracy,convergence, and computational complexity of these two methods by usingthem to solve second-order nonlinear equations using a new differential operator for the second-order equation. We also used both methods to solvesecond-order nonlinear differential equations.
Keywords: Differential transformation method; Adomian decomposition method; second-order ordinary differential equations.